Mediating Effect of Organizational Commitment on The Influences of Work-Family Conflict and Organizational Culture on Organizational Citizenship Behaviour - Muhammad Adrian Bagaskara; Anik Herminingsih (Asian Journal of Social and Humanities, 2024)
PT Madya Utama Lima is a company engaged in the field of coal mining management and mining contractor service provider. This study aims to examine the mediating role of organizational commitment on the relationships between work-family conflict and organizational culture with organizational citizenship behavior (OCB) at PT Madya Utama Lima. The research employs a quantitative approach with a survey method, involving 60 permanent employees as respondents. Data were analyzed using the structural equation model (SEM) with Smart PLS software. The findings indicate that work-family conflict negatively affects both organizational commitment and OCB, while organizational culture positively affects organizational commitment and OCB. Furthermore, organizational commitment significantly mediates the negative impact of work-family conflict and the positive impact of organizational culture on OCB. The results highlight the importance of enhancing organizational commitment to mitigate work-family conflict and leverage organizational culture for improved OCB. This research provides practical insights for organizations to create supportive policies and strengthen their cultural values, contributing to increased employee performance and organizational effectiveness.